The British commercial houses in Peru and Chile between the two world wars: success and failure - Miller, Rory M. (Estudios de Economía, 2016)
The previously successful British merchant houses on the west coast of South America faced significant problems between the two world wars. Earlier historians have referred to difficulties such as the volatility of commodity prices, the organisation and structure of the firms, and changes in patterns of trade. This paper, instead, compares their different experiences on the basis of archives from the merchants and their banks, concluding that their response to crisis differed, depending on the manner and extent of diversification, their core expertise, the quality of their management, and the support of their banks. The outcomes varied from outright failure to continued growth, with the two largest firms struggling to survive and adapt to the new business environment.